Aspek Qira’at dalam al-Qur’an - Ahmad Fauzan Pujianto (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The differences of the Arabs brought about the consequences of the birth of various qira'ah in reciting the Qur'an. This is actually natural, therefore, the Prophet himself justified the pronunciation of the Qur'an with various qira'ah. Qira'at qur'an experienced a golden age of existence from the 1st century to the 9th century Hijri, precisely until the time of Ibn Jazari (d. 833 H/1429 AD). After that until the decade of the 1970s gradually experienced a period of decline in the Islamic world including Indonesia. Majma' al-Buhuth (Research Institute) al-Azhar Cairo in its Conference on 20-27 April 1971 AD, And the Central Indonesian Ulema Council on March 2, 1983 decided that Qira'at qur'an was not the result of Ijtihad, but Tauqifi which adheres to the history of mutawatir, and appealed to all Islamic countries to encourage the study of Qira'at in special educational institutions managed by Qira'at scholars who are trusted expertise. This article presents a brief study of the science of Qira'at, ranging from understanding, the status of verses that have different readings and forms to penance to the imam of qira'at.